2021
DOI: 10.1021/acscatal.1c04239
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Formal Cross-Electrophile Coupling of Alcohols with Aryl Halides

Abstract: Direct coupling of unactivated alcohols remains a challenge in current synthetic chemistry. We herein demonstrate a strategy building upon in situ halogenation/reductive coupling of alcohols with aryl halides to forge Csp2–Csp3 bonds. The combination of 2-chloro-3-ethylbenzo­[d]­oxazol-3-ium salt (CEBO) and TBAB as the mild bromination reagents enables rapid transformation of a wide range of alcohols to their bromide counterparts within one to 5 min in CH3CN and DMF, which is compatible with the Ni-catalyzed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Gong demonstrated a strategy of in situ halogenation/reductive coupling of alkyl alcohols with aryl halides (Scheme 34). 71 They found that the mixture of 2-chloro-3-ethylbenzo[d]oxazol-3-ium salt (CEBO) and TBAX (X = B or C) enabled rapid transformation of a wide range of alcohols into their halide counterparts within 1 to 5 min in CH3CN and DMF at room temperature, which is compatible with the Ni-catalyzed cross-electrophile coupling conditions. 3-Ethylbenzo[d]oxazol-2(3H)-one (BEO), as a coproduct of halogenation step, served as an important additive.…”
Section: Scheme 33 Photo-induced Carbene-mediated Deoxygenative Aryla...mentioning
confidence: 90%
See 1 more Smart Citation
“…Gong demonstrated a strategy of in situ halogenation/reductive coupling of alkyl alcohols with aryl halides (Scheme 34). 71 They found that the mixture of 2-chloro-3-ethylbenzo[d]oxazol-3-ium salt (CEBO) and TBAX (X = B or C) enabled rapid transformation of a wide range of alcohols into their halide counterparts within 1 to 5 min in CH3CN and DMF at room temperature, which is compatible with the Ni-catalyzed cross-electrophile coupling conditions. 3-Ethylbenzo[d]oxazol-2(3H)-one (BEO), as a coproduct of halogenation step, served as an important additive.…”
Section: Scheme 33 Photo-induced Carbene-mediated Deoxygenative Aryla...mentioning
confidence: 90%
“…Gong has demonstrated a strategy that involves in situ halogenation/reductive coupling of alkyl alcohols with aryl halides (Scheme 34). 71…”
Section: Short Review Synthesismentioning
confidence: 99%
“…One method involves the in situ conversion of the hydroxyl motif into the corresponding iodide or bromide, which subsequently reacts via metal‐catalysed coupling in a one‐pot cascade strategy. Inspired by this concept, Gong [47] and Weix [48] concurrently reported Ni‐catalysed methodologies for the formal cross‐coupling of alcohols with aryl halides (Gong) and aryl/alkenyl halides (Weix) (Scheme 29). The former employed 2‐chloro‐3‐ethylbenzo[ d ]‐oxazol‐3‐ium salts (CEBO) 61 as in situ halogenating reagents, while the latter utilised Hendrickson's POP reagent 62 [49] to achieve this goal.…”
Section: Deoxygenative C−c Bond Formationmentioning
confidence: 99%
“…One method involves the in situ conversion of the hydroxyl motif into the corresponding iodide or bromide, which subsequently reacts via metal-catalysed coupling in a one-pot cascade strategy. Inspired by this concept, Gong [41] and Weix [42] concurrently reported Ni-catalysed methodologies for the formal crosscoupling of alcohols with aryl halides (Gong) and aryl/alkenyl halides (Weix) (Scheme 23). The former employed 2-chloro-3ethylbenzo[d]-oxazol-3-ium salts (CEBO) 34 as in situ halogenating reagents, while the latter utilised Hendrickson's POP reagent 35 [43] to achieve this goal.…”
Section: Via Transition Metal Catalysismentioning
confidence: 99%